The Effect of Image Media on Learning Outcomes of Class V MIS Students in Siboruangin Village in Information Communication Technology (ICT) Subjects - Baginda Harahap (Jurnal Informatika, 2022)
Student learning outcomes in the control class with conventional learning on the subject of Information and Communication Technology (ICT) material for class V MIS Siboruangin Village got an average pretest score of 41.2 with a standard deviation of 18.102 and a variance of 327.67,while the average post-test score was 67. ,6 with a standard deviation of 12.6754 and a variance of 160.667 from a total of 25 students. Student learning outcomes in the experimental class using image media in Information and Communication Technology subjects for class V MIS Siboruangin Village got an average posttest score of 42.4 with a standard deviation of 13.316656 and a variance of 177.33333 while the average post-test score was 76 with a standard deviation of 12.24744871 and a variance of 150 from a total of 25 students